2016
DOI: 10.1021/acs.jpclett.6b00179
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal Interaction and Propeller Chirality of Hexaarylbenzenes. Dynamic Domino Inversion Revealed by Combined Experimental and Theoretical Circular Dichroism Studies

Abstract: Hexaarylbenzenes (HABs) have greatly attracted much attention due to their unique propeller-shaped structure and potential application in materials science, such as liquid crystals, molecular capsules/rotors, redox materials, nonlinear optical materials, as well as molecular wires. Less attention has however been paid to their propeller chirality. By introducing small point-chiral group(s) at the periphery of HABs, propeller chirality was effectively induced, provoking strong Cotton effects in the circular dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 27 publications
5
52
0
Order By: Relevance
“…Note that although C and CC conformers are diastereomers of each other, the point chirality at the periphery (on the order of <1 m −1 cm −1 ) is negligible compared with the CD derived from the propeller shape (which is typically on the order of >100 m −1 cm −1 , owing to the strong excitonic coupling). The value of ±0.003 was obtained by extrapolation of the observed g factor values to infinite pressure, which agrees well with the experimental g value at very low temperature for H6 . (3) Experimentally, we observed two distinct pressure‐dependent regimes for the g factors, both of which provided good linear correlations within an experimental error.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Note that although C and CC conformers are diastereomers of each other, the point chirality at the periphery (on the order of <1 m −1 cm −1 ) is negligible compared with the CD derived from the propeller shape (which is typically on the order of >100 m −1 cm −1 , owing to the strong excitonic coupling). The value of ±0.003 was obtained by extrapolation of the observed g factor values to infinite pressure, which agrees well with the experimental g value at very low temperature for H6 . (3) Experimentally, we observed two distinct pressure‐dependent regimes for the g factors, both of which provided good linear correlations within an experimental error.…”
Section: Resultssupporting
confidence: 87%
“…(2) We assumed the g factors for these conformers as 0, + g 0 (=+0.003), and − g 0 (=−0.003), respectively. These conformation‐dependent changes in the CD spectra were also supported by quantum chemical calculations . Note that although C and CC conformers are diastereomers of each other, the point chirality at the periphery (on the order of <1 m −1 cm −1 ) is negligible compared with the CD derived from the propeller shape (which is typically on the order of >100 m −1 cm −1 , owing to the strong excitonic coupling).…”
Section: Resultsmentioning
confidence: 53%
See 2 more Smart Citations
“…Comparison of stepwise produced 22* to ( R , R , R , R , R , R )‐ 22 , by both optical rotation and circular dichroism (Figure ), revealed that the R configured stereogenic centres created on ( S )‐CBS catalysed reduction do not control the selectivity of reduction with NaBH 4 . In addition, the similarity of the CD spectrum of ( R )‐ 16 to that of ( R , R , R , R , R , R )‐ 22 suggests that, under the conditions used for the recording of these spectra, the para‐ substituted stereogenic centres of the latter do not induce a preference for M or P propeller chirality in the pentaarylcyclopentadienyl moiety …”
Section: Resultsmentioning
confidence: 99%